The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5923/j.als.20110101.01
|View full text |Cite
|
Sign up to set email alerts
|

OlfactionDB: A Database of Olfactory Receptors and Their Ligands

Abstract: Odorants are volatile molecules that efficiently carry chemical information, providing one of the main ways for communicating with the environment in all kingdoms of life. In the other hand, mammalian genomes codify for hundreds of olfactory receptors (ORs), e.g. about 400 in human and more than 1000 in mouse, underlying the crucial role of the sense of smell during evolution. Therefore, the olfactory system is capable to discriminate between ~10,000 different odors. The possibility of collecting and compiling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…The expression of OR1A1 was the highest among the tested ORs, so we performed additional studies. Immunoblotting analysis confirmed that OR1A1 was expressed in the plasma membrane of HepG2 cells, and a previous study demonstrated that (−)-carvone was a strong ligand for OR1A1 (Saito et al, 2009), with a halfmaximal effective concentration of approximately 0.5 M (Modena et al, 2011). The widely distributed natural aroma terpenoid compound, (−)-carvone, which is especially abundant in plant essential oils such as spearmint (Fichan et al, 1999), exhibits antimicrobial, antioxidant, and anti-inflammatory activities (Aggarwal et al, 2002;Elmastas et al, 2006;Terracciano et al, 2006).…”
Section: Introductionsupporting
confidence: 65%
“…The expression of OR1A1 was the highest among the tested ORs, so we performed additional studies. Immunoblotting analysis confirmed that OR1A1 was expressed in the plasma membrane of HepG2 cells, and a previous study demonstrated that (−)-carvone was a strong ligand for OR1A1 (Saito et al, 2009), with a halfmaximal effective concentration of approximately 0.5 M (Modena et al, 2011). The widely distributed natural aroma terpenoid compound, (−)-carvone, which is especially abundant in plant essential oils such as spearmint (Fichan et al, 1999), exhibits antimicrobial, antioxidant, and anti-inflammatory activities (Aggarwal et al, 2002;Elmastas et al, 2006;Terracciano et al, 2006).…”
Section: Introductionsupporting
confidence: 65%
“…This was done by using an online odorant database, OlfactionDB (Modena et al, 2011). Although limited, this database, which is manually curated from the literature, provides information about these odorant molecules and their interactions with odorant receptors (Modena et al, 2011). Since the aim here was to identify odorants that are known to interact with ORs and which might also interact with OATs, it was expected that this database would be useful for virtual screening with the pharmacophore model.…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacophore model-which has as a basis OR ligands capable of interacting with OATs in transport assays-was then used in a virtual screen of a structural library of odorant molecules which have been shown to bind ORs with an EC 50 of ;1 mM to ;1 mM. This was done by using an online odorant database, OlfactionDB (Modena et al, 2011). Although limited, this database, which is manually curated from the literature, provides information about these odorant molecules and their interactions with odorant receptors (Modena et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations